PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN - Jumi Raditiana (Jurnal Ilmiah Wahana Akuntansi, 2019)
This research aimed to examine the effect of corporate governance, firm size, and audit quality on the integrity of financial statements. The sample of 27 firms used in this research is publicly traded banking companies listed in Indonesia Stock Exchange before 2012 with the observation period from 2012 to 2015 and is determined by purposive sampling method. The analysis technique used is panel data regression through E-views software 9. This research uses fixed effect model from the result of Chow test and Hausman test. The result of this research indicated that simultaneously, audit quality, corporate governance, and firm size influence the integrity of financial statements. While partially, corporate governance and firm size proved not to affect the integrity of financial statements. As for audit quality has a positive impact on the integrity of financial statements.